The Impact of Different Bracing Ratios on the Structural Performance of Planar Steel Frames - Nguyen, Huy-Phuoc; Nguyen, Phu-Cuong (Engineering, Technology & Applied Science Research, 2025)
Bracing systems are a part of steel construction projects, designed to increase stability and reduce lateral displacement. Rather than increasing the section size or reducing the span, bracing systems provide a more efficient solution. Diagonal, inverted V, X, and K bracing are the most commonly encountered configurations in practice, each of which affects structural performance differently in terms of stability and capacity. This study examines the effects of varying bracing ratios on the performance of planar steel frames using these four bracing types. Ensuring both strength and stability, especially against buckling, is critical in the design of steel structures. Using SAP2000, the buckling behavior of multi-story planar steel frames with different bracing ratios was simulated, in order to analyze the structural performance thoroughly. The results contribute to more efficient bracing arrangements that ensure safety while minimizing material usage, construction costs, and time, all without compromising aesthetics. These findings will help designers and investors optimize structural bracing for better results.